Peran Strategi Pemasaran Dalam Meningkatkan Omzet Penjualan Nymaz Hijab Kecamatan Ngasem Kabupaten Kediri - Avinka, Dhabita Reyna Dianis; Saka, Dijan Novia; Lestari, Erawati Dwi; Subandono, Agus (Al-Muraqabah: Journal of Management and Sharia Business, 2024)
This study aims to examine the role of marketing strategies in increasing the sales turnover of Nymaz Hijab products in Ngasem District, Kediri Regency. This research uses a qualitative method using primary data obtained from interviews and direct observation with the owner, employees, and consumers of Nymaz Hijab. Secondary data used is information from the internet and Nymaz Hijab's social media accounts. The results showed that Nymaz Hijab uses marketing strategies which include attention to product quality, always updating products, determining prices based on product prices from the center by considering other costs, and active promotion through social media such as Instagram, WhatsApp, and TikTok. However, Nymaz Hijab needs to pay attention to market selection to determine its target market. With the marketing strategy carried out, Nymaz Hijab succeeded in increasing sales turnover from IDR 278,050,000 in 2022 to IDR 289,950,000 in 2023. In addition, business owners also sometimes hold product sales to attract consumer interest. Thus, an optimized marketing strategy can make a significant contribution in increasing the company's sales turnover.